The potential use of partially sulfonated polystrene (ePS) in the pretreatment of lignocellulosic biomass - De Luna, Marjorie S. (2009)
This study evaluates the degradation of cellulose by viscometry principle utilizing Whatmann ashless filter paper as cellulose sample. Sulfuric Acid (H2SO4) and Polystyrene (sPS) resin were used as dissolution catalysts. The study investigates the behavior of cellulose in H2S and sPS solution and the potential of sPS resin in the degradation of cellulose sample. Based from the results of the study, addition of urea improves dissolution of cellulose. Whatmann ashless filter paper treated with H2SO4 was completely dissolved in 6%(w/v)NaOH/4%(w/v)urea/H2O aqueous solution while the filter paper treated with sPS resin achieved incomplete dissolution. from viscosity measurements, a decrease of 61% and 40% H2SO4- and sPS-treated filter paper respectively, were obtained for a treatment time of 116 hours. The intrinsic fluidity curves generated in the study showed a straight line trend, typical for depolymerization reactions. This indicates that the chains of Whatmann ashless filter paper were continuously broken down for the H2SO4- and sPS-treated ashless filter paper. Thus, the application of sPS resin in the future studies using real lignocellulosic biomass offers a promising field of study in the pretreatment operations in the conversion of lignocellulosic biomass to ethanol.